Building resilient partnerships: How businesses and nonprofits create the capacity for responsiveness - Taylor, Lauren A.; Aveling, Emma-Louise; Roberts, Jane; Bhuiya, Nazmim; Edmondson, Amy; Singer, Sara (Frontiers in Health Services, 2023)
Increasingly, businesses are eager to partner with nonprofit organizations to benefit their communities. In spite of good intentions, differences between nonprofit and business organizations can limit the ability of potential partnerships to respond to a changing economic and public health landscape. Using a retrospective, multiple-case study, we sought to investigate the managerial behaviors that enabled businesses and nonprofits to be themselves together in sustainable partnerships. We recruited four nonprofit-business partnerships in the Boston area to serve as cases for our study. Each was designed to address social determinants of health. We thematically analyzed qualitative data from 113 semi-structured interviews, 9 focus groups and 29.5 h of direct observations to identify organizational capacities that build resilient partnerships. Although it is common to emphasize the similarities between partners, we found that it was the acknowledgement of difference that set partnerships up for success. This acknowledgement introduced substantial uncertainty that made managers uncomfortable. Organizations that built the internal capacity to be responsive to, but not control, one another were able to derive value from their unique assets.